2006
DOI: 10.1179/016164106x98279
|View full text |Cite
|
Sign up to set email alerts
|

Progressive necrotizing myelopathy: part of the spectrum of neuromyelitis optica?

Abstract: This case series reviews the clinical, radiographic and laboratory findings of five patients with progressive idiopathic myelopathy with evidence of cord necrosis who presented in our institution over a 5 year period ending in May 2005. Patients fulfilling the following criteria were included: (1) presentation with myelopathy without overt visual involvement at initial presentation; (2) demonstration with magnetic resonance imaging (MRI) of contiguously abnormal signal in the spinal cord spanning at least thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…[13][14][15] NMO-IgG is also positive in 25% of recurrent ON patients without MS and 38% to 80% of patients with isolated LETM. [14][15][16][17] Evidence is mounting that NMO is a distinct condition, rather than simply a rare subtype of MS. In support of that idea, we found a greater degree of retinal damage after ON in NMO than in MS. Our study did not have sufficient power to definitively determine whether unaffected NMO eyes are abnormal, but retinal damage in NMO seems to be predominantly or exclusively the result of destructive ON episodes.…”
Section: Figure 2 Box Plots Of Macular Volume By Disease Type and Optmentioning
confidence: 99%
“…[13][14][15] NMO-IgG is also positive in 25% of recurrent ON patients without MS and 38% to 80% of patients with isolated LETM. [14][15][16][17] Evidence is mounting that NMO is a distinct condition, rather than simply a rare subtype of MS. In support of that idea, we found a greater degree of retinal damage after ON in NMO than in MS. Our study did not have sufficient power to definitively determine whether unaffected NMO eyes are abnormal, but retinal damage in NMO seems to be predominantly or exclusively the result of destructive ON episodes.…”
Section: Figure 2 Box Plots Of Macular Volume By Disease Type and Optmentioning
confidence: 99%
“…Kuroda et al reported the case of a patient with acute necrotizing myelopathy and occult cancer in which IgG, myelin basic protein and activated helper T cells were increased in the CSF at onset, suggesting a mechanism of autoimmunity [12]. Some reports have suggested that idiopathic PNM is related to NMO based on the elevated serum NMOIgG or the presence of a subclinical optic nerve lesion [7,13]. In the present case, serum NMO-IgG was negative.…”
Section: Discussionmentioning
confidence: 58%
“…These cases are strikingly similar to NMO, whose pathology also involves both gray-and white-matter necrosis as well as vascular hyalinization (Lucchinetti et al, 2002). The potential relationship between paraneoplastic myelopathy and NMO has previously been suggested (Katz and Ropper, 2000;Okai et al, 2006). Vascular hyalinization, frequently observed in cases of necrotizing myelopathy, is a pathologic hallmark of NMO.…”
Section: Association With Neuromyelitis Opticamentioning
confidence: 63%